Association of British Clinical Diabetologists and Renal Association guidelines on the detection and management of diabetes post solid organ transplantation. Issue 6 (11th February 2021) - Chowdhury, Tahseen A.; Wahba, Mona; Mallik, Ritwika; Peracha, Javeria; Patel, Dipesh; De, Parijat; Fogarty, Damian; Frankel, Andrew; Karalliedde, Janaka; Mark, Patrick B.; Montero, Rosa M.; Pokrajac, Ana; et al.
Abstract: Post‐transplant diabetes mellitus (PTDM) is common after solid organ transplantation (SOT) and associated with increased morbidity and mortality for allograft recipients. Despite the significant burden of disease, there is a paucity of literature with regards to detection, prevention and management. Evidence from the general population with diabetes may not be translatable to the unique context of SOT. In light of emerging clinical evidence and novel anti‐diabetic agents, there is an urgent need for updated guidance and recommendations in this high‐risk cohort. The Association of British Clinical Diabetologists (ABCD) and Renal Association (RA) Diabetic Kidney Disease Clinical Speciality Group has undertaken a systematic review and critical appraisal of the available evidence. Areas of focus are; (1) epidemiology, (2) pathogenesis, (3) detection, (4) management, (5) modification of immunosuppression, (6) prevention, and (7) PTDM in the non‐renal setting. Evidence‐graded recommendations are provided for the detection, management and prevention of PTDM, with suggested areas for future research and potential audit standards. The guidelines are endorsed by Diabetes UK, the British Transplantation Society and the Royal College of Physicians of London. The full guidelines are available freely online for the diabetes, renal and transplantation community using the link below. The aim of this review article is to introduce an abridged version of this new clinical guideline ( https://abcd.care/sites/abcd.care/files/site_uploads/Resources/Position‐Papers/ABCD‐RA%20PTDM%20v14.pdf ).